Rancang Bangun Sistem Informasi Pemesanan Makanan Dan Minuman Berbasis Web S’cafe - Frengki Pernando (Jurnal Kajian Teknik Elektro, 2025)
S’Café is a business establishment that serves food and beverage orders for customers. Ordering is an activity carried out by customers prior to the purchasing process. To achieve customer satisfaction, a company must have an ordering system that is efficient, fast, and accurate. The research method used in this study is a data collection method that includes observation, interviews, and literature review in order to obtain relevant information that supports the research. Meanwhile, the software development method applied in this study is the waterfall method, which consists of the stages of analysis, design, implementation, testing, and system maintenance. Currently, S’Café faces difficulties in handling orders because it still uses a manual or conventional recording system. This condition causes customers to wait a long time to place their orders, while staff also experience difficulties in recording orders manually using paper, which is prone to errors and data loss. Manual order recording is considered inefficient in terms of time and data accuracy. Therefore, to improve service quality and customer satisfaction, a web-based food ordering information system is designed using PHP and MySQL.